The Role of the United Nations in Realizing the Right of the Palestinian People to Self-Determination - Abdelrahman Alasttal; Abdul Maasba Magassing (حقوق بشر)
This study aims to analyze the historical situation of the Palestinian right to self-determination to find out the reasons for its emergence and the obstacles that prevent its realization, as well as the scope of the role of the United Nations in this regard. The methodology refers to an analytical study and a statutory and a conceptual approach. The study found that the United Nations had solved the Question of the Jews by achieving self-determination by granting them the land of the Palestinians and accepting their state's membership in the United Nations a year after its establishment. On the contrary, the United Nations created the Question of the Palestinians and caused their right to self-determination to emerge by giving their land to outsiders, as well as its refusal to accept full membership of the modern Palestinian state in the United Nations. It also left the Palestinian Question without providing any effective solution to it, due to the inability of the Security Council to take any action against Israel due to the full American support for it. The study suggests that the Palestinians have the right to bypass the Security Council and turn to the General Assembly according to Resolution 377 A, called the "Uniting for Peace," and resorting to all means of struggle to realize their right to self-determination.